An overview of the success of the “PADAMU DHIVA” program on adherence to consuming ARVs for HIV-AIDS patients at the Balowerti Primary Health Care Center - Twoti Dika Parmanasari; Hanie Kusuma Wardani (Strada Journal of Pharmacy, 2023)
Adherence to anti-retroviral (ARV) treatment in HIV/AIDS patients is essential to suppress the growth of the virus optimally and improve the patient's quality of life. HIV/AIDS patients can only miss 1-2 doses within one month of consuming ARVs, meaning their adherence to ARVs must be more than 95%. A medication assistance program for HIV/AIDS patients on ARV (Padamu Dhiva) was created to achieve and maintain this high adherence. This study aims to provide an overview of the successful implementation of the "Padamu Dhiva" Program on the commitment to consuming ARVs in HIV/AIDS patients. This research is a quantitative descriptive study conducted on 92 HIV/AIDS patients at the Balowerti Primary Health Care Center in implementing the "Padamu Dhiva" Program, start from January to December 2022. Data obtained on increasing patient compliance from groups 2 and 3 adherence values to compliance value 1 was 90%. Pharmacists are also greatly facilitated by the "Padamu Dhiva" Program, the amount of remaining medication the patient has per day can be known directly, and a warning appears for the pharmacist when it is time to give a reminder to the patient. The system already connected to the Whatsapp application also makes it easier for pharmacists to contact patients individually. With this program, the incidence of loss to follow-up shows a decrease of 33.3%. The "Padamu Dhiva" program increases adherence to ARV in HIV/AIDS patients at the Balowerti Primary Health Care Center.